Relationship Analysis between Demographic Factors, Job Satisfaction, and Job Performance among Formal Employees in DKI Jakarta - Suryawijaya, Marwah; Bekti, Rudy (Journal of Business and Management, 2016)
Abstract. The primary resource to support the productivity of innovative, high quality, and competitive product is proven gained from highly performing employees. Any aspect related to high performance thus has become an interest to organizations to stay in the business and protect their profit. Some studies and wisdom indicate that job satisfaction is one of the biggest aspects affecting the performance of an employee. Â DKI Jakarta is the capital city of Indonesia. Not only as the central of the government, but also as the central of economics, businesses, and employments. In 2015, formal workers took 73% of the total working citizen, which indicates as the highest proportion of overall working citizen in DKI Jakarta comparing to informal workers. The growth of formal worker is seen to be the biggest with an increase percentage of 10.26% in one year, it means that 344 thousands of people were get employed within a year. Therefore, this research was constructed to enrich and complete the scarcity in previous studies regarding the relationship between job satisfaction and job performance. The specific type of object was formal worker in DKI Jakarta area. The study was executed by distributing questionnaires in regard to demographic factors, job satisfaction, and job performance to 258 respondents who are currently employed as formal workers. The data collected was analyzed using Microsoft Excel, SPSS 20, and processed through Descriptive Analysis, Chi Square Analysis, T-Test, and Simple Linear Regression. The result found that formal workersâ€™ demographic factors (age, gender, and education level) of DKI Jakarta are not associated with Job Satisfaction. While the relationship between job satisfaction and job performance was found positively related. Not only relations, the author discovered that whenever oneâ€™s job satisfaction increase as 1 unit, his performance at work will also increase as 0,738 unit. Between three dimensions of job performance, contextual performance takes the highest position that gains most influence by job satisfaction.Keyword: Job Satisfaction, Job Performance, Task Performance, Contextual Performance, Counterproductive Work Behavior, Demographic Factors, Human Resource Management